1999
DOI: 10.1073/pnas.96.6.2988
|View full text |Cite
|
Sign up to set email alerts
|

Stable transduction of quiescent CD34+CD38human hematopoietic cells by HIV-1-based lentiviral vectors

Abstract: We compared the efficiency of transduction by an HIV-1-based lentiviral vector to that by a Moloney murine leukemia virus (MLV) retroviral vector, using stringent in vitro assays of primitive, quiescent human hematopoietic progenitor cells. Each construct contained the enhanced green f luorescent protein (GFP) as a reporter gene. ؉ and CD34 ؉ CD38 ؊ cells (13.5 ؎ 2.5%, n ‫؍‬ 11 and 12.2 ؎ 9.7%, n ‫؍‬ 4, respectively). The lentiviral vector is clearly superior to the MLV vector for transduction of quiescent, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
227
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 387 publications
(239 citation statements)
references
References 52 publications
11
227
0
1
Order By: Relevance
“…In these tissues, the level of gene marking was in the range of 3-to 2200-fold higher compared to other organs; in addition, the levels of mRNA EGFP transcripts were in the range of 11-to 680-fold higher (Figure 5a and b) ( Table 5). In nonabdominal organs, the level of gene transduction was on average seven-fold (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] higher in the animals injected at 40 versus 60 days gestation. No mRNA EGFP transcripts were found in nonabdominal organs of the animals injected at 60 days gestation (Figure 5b).…”
Section: Comparison Of the Levels Of Gene Transcription Between Fetusmentioning
confidence: 99%
See 1 more Smart Citation
“…In these tissues, the level of gene marking was in the range of 3-to 2200-fold higher compared to other organs; in addition, the levels of mRNA EGFP transcripts were in the range of 11-to 680-fold higher (Figure 5a and b) ( Table 5). In nonabdominal organs, the level of gene transduction was on average seven-fold (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] higher in the animals injected at 40 versus 60 days gestation. No mRNA EGFP transcripts were found in nonabdominal organs of the animals injected at 60 days gestation (Figure 5b).…”
Section: Comparison Of the Levels Of Gene Transcription Between Fetusmentioning
confidence: 99%
“…Several studies have demonstrated efficient gene transfer using lentiviral vectors in a variety of animal models [2][3][4] including non-human primates. 5,6 Lentiviral vectors can efficiently mediate gene transfer in a wide range of dividing and nondividing quiescent cells, 7 and maintain gene expression for extended periods of time. Differences in the transcriptional pattern in transduced tissues that may occur under varied experimental conditions include the type of viral construct used, the viral titer transferred, and the timing of fetal gene delivery, all of which can help to determine the best conditions for future human application.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Among the current technologies for gene transfer of leukemia cells, the latest generation of HIV-1-based lentiviral vectors represent the most efficient tool for their reported ability to transduce with stability, a wide variety of cell types in significant percentages. [7][8][9][10][11][12][13][14][15][16][17] B-cell precursor (BCP) blasts are very fragile and difficult to maintain alive in culture conditions. 18 The best available results so far for gene transduction have been obtained with second-generation lentiviral vectors monitoring the expression of the CD80 transgene up to 48 h. 5 More recently, second-generation lentiviral vectors have been further modified by deleting a portion of the U3 LTR region in the so-called self-inactivating vector (SIN) with improved safety, 8,9,15,19,20 and by the introduction of two cis-acting elements, one derived from the pol sequence, called central polypurine tract sequence (cPPT), 11,21,22 and the other, termed Wpre, obtained from the genome of the woodchuck hepatitis virus, both believed to increase transgene expression.…”
mentioning
confidence: 99%
“…All vectors carry the GFP marker gene and were kindly provided by Dr Naldini, Torino, Italy, and are described elsewhere. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] Viral vector particles were generated by cotransfection of the VSV containing plasmid pMD-G, the packaging construct pCMVdR8.74 and the indicated transfer constructs into 293T cells, followed by determination of concentration of particles by ultracentrifugation, as previously described. 65 Viral titers were evaluated by infecting a known number of REH cells with different volumes of viral vector preparations in a 200 ml volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation